How to Improve Academic Performance For Employed Students? - Ilhami, Susanti Dwi; Rikah; Rumaji; Setiadi, Teguh (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
Working students generally find it difficult to divide their time between work and education, resulting in obstacles to students' educational performance. Students often prioritize work over education. Employed students have lower life satisfaction This hampers the university's performance in achieving its goals. The aim of the research is to determine the effect of dual role conflict experienced by working students on academic performance with life satisfaction as a mediating variable. The type of research is quantitative research with an explanatory approach. Research data collection techniques through distributing questionnaires. The sample for this research is all students who study and work at YPPI Rembang University. The sampling technique used a saturated sample of 60 students. Technical data analysis uses PLS-SEM assisted by Smartpls software. The research results show that dual role conflict has no effect on academic performance and life satisfaction. However, life satisfaction influences academic performance. In this study, it was not proven that life satisfaction can mediate the effect of dual role conflict on academic performance. Students must increase their life satisfaction so that their academic achievements become better by achieving cum laude and graduating on time.